2014
DOI: 10.1002/pip.2483
|View full text |Cite
|
Sign up to set email alerts
|

p‐CuO/n‐Si heterojunction solar cells with high open circuit voltage and photocurrent through interfacial engineering

Abstract: Heterojunction solar cells of p-type cupric oxide (CuO) and n-type silicon (Si), p-CuO/n-Si, have been fabricated using conventional sputter and rapid thermal annealing techniques. Photovoltaic properties with an open-circuit voltage (V oc ) of 380 mV, short circuit current (J sc ) of 1.2 mA/cm 2 , and a photocurrent of 2.9 mA/cm 2 were observed for the solar cell annealed at 300°C for 1 min. When the annealing duration was increased, the photocurrent increased, but the V oc was found to reduce because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 43 publications
9
65
0
Order By: Relevance
“…A significant increase in electrical parameters, namely FF-fill factor, J sc -short-circuit current density and PCE was observed with increasing temperature. The device performance is high at higher temperature due to the better crystal and interface quality as described in a previous study as well [26]. The best-achieved PCE is 0.08% which is primarily due to low J sc and V oc .…”
Section: Resultssupporting
confidence: 54%
“…A significant increase in electrical parameters, namely FF-fill factor, J sc -short-circuit current density and PCE was observed with increasing temperature. The device performance is high at higher temperature due to the better crystal and interface quality as described in a previous study as well [26]. The best-achieved PCE is 0.08% which is primarily due to low J sc and V oc .…”
Section: Resultssupporting
confidence: 54%
“…Indeed, a few recent studies from Dalapati and coworkers demonstrated the possibility of using CuO thin films as efficient absorbers, including doping and codoping, getting 2% PCE. [98,99] The PCE is comparable with results obtained from Cu 2 O thin films. However, the main crit ical point of this research is the use of Si substrate as ntype counterpart to CuO, while most of the research on Earth abun dant solar cells aims at removing the use of silicon due to its high production/processing/manufacturing costs.…”
Section: Wwwadvancedsciencenewscomsupporting
confidence: 79%
“…This increase in V oc and I sc indicates the conversion efficiency improvement in the device with the increase in copper concentration. The enhanced performance of device due to the increase in Cu concentration can be attributed due to the crystalline improvement and the change in barrier heights [31]. Enhancement in grain size due to the increased Cu concentration can increase the carrier transport by reducing the grain boundaries.…”
Section: Photoresponse Studymentioning
confidence: 99%
“…Similarly, the heterojunction of p-CuO/n-Si is also attracted owing to the easy fabrication of CuO thin film on wide variety of substrates. Even though the CuO is attractive to form heterojunction with silicon, the works on p-CuO/n-Si are limited [30,31] Hence, in this work, we have fabricated p-CuO/n-Si heterojunction solar cells using SILAR-prepared CuO thin films and studied the solar cell properties.…”
Section: Introductionmentioning
confidence: 99%